Seasonal Acclimation Modulates the Impacts of Simulated Warming and Light Reduction on Temperate Seagrass Productivity and Biochemical Composition - Beca-Carretero, Pedro; Azcárate-García, Tomás; Julia-Miralles, Marc; Stanschewski, Clara S.; Guihéneuf, Freddy; Stengel, Dagmar B. (Frontiers in Marine Science, 2021)
Increases in seawater temperature and reduction in light quality have emerged as some of the most important threats to marine coastal communities including seagrass ecosystems. Temperate seagrasses, including Zostera marina, typically have pronounced seasonal cycles which modulate seagrass growth, physiology and reproductive effort. These marked temporal patterns can affect experimental seagrass responses to climate change effects depending on the seasons of the year in which the experiments are conducted. This study aimed at evaluating how seasonal acclimatisation modulates productivity and biochemical responses of Zostera marina to experimental warming and irradiance reduction. Seagrass shoots were exposed to different temperatures (6, 12, 16, 20 and 24 °C), combined with high (180 μmol photons m-2 s-1) and low (60 μmol photons m-2 s-1) light conditions across four seasons (spring: April, summer: July, and autumn: November 2015, and winter: January 2016). Plants exhibited similar temperature growth rates between 16 and 20 °C; at 24 °C, a drastic reduction in growth was observed; this was more accentuated in colder months and under low irradiance conditions. Higher leaf growth rates occurred in winter while the largest rhizomes were reached in experiments conducted in spring and summer. Increases in temperature induced a significant reduction in polyunsaturated fatty acids (PUFA), particularly omega-3 (n-3 PUFA). Our results highlight that temperate seagrass populations currently living under temperature limitation will be favoured by future increases in sea surface temperature in terms of leaf and rhizome productivity. Together with results from this study on Z. marina from a temperate region, a wider review of the reported impacts of experimental warming indicates the likely reduction in some compounds of nutritional importance for higher trophic levels in seagrass leaves. Our results further demonstrate that data derived from laboratory-based studies investigating environmental stress on seagrass growth and acclimation, and their subsequent interpretation, are strongly influenced by seasonality and in situ conditions that precede any experimental exposure.